Khoe, San, Coloured, controvert or conform: Physical attributes influencing the formation of cultural identity in ""Coloured"" women of the Western and Northern Cape - Kotze, Annelize (Department of Archaeology, 2024)
This study sets out to investigate how physical attributes such as hair texture, the colour of your skin and even body structure, influences one's sense of self and ultimately, how this informs cultural identity formulation. The focus of the study was on women from the Northern and the Western Cape to gauge whether these formulations of cultural identity are also influenced by geographical spaces. The Khoe and San have been studied, misrepresented and misinterpreted for many years, to the extent that they have become protective of their time and their information, and rightfully so. This also holds for people classified under the Apartheid regime as Coloured. Racist, derogatory past classificatory terms which refer to Khoe and San persons, still haunt many people to the extent that they have chosen to disassociate from their indigenous ancestry and internalize and embrace the Apartheid classificatory term Coloured. This very same classification and categorisation which today, under the new dispensation, is still used to marginalise people of colour on a racial basis. In certain communities the Khoisan revivalist movement has seen an uprising in individuals claiming their indigenous Khoisan identity and their rights as indigenous people in the postapartheid South Africa. This study was performed through oral interviews with over 100 women, and a few men, from various geographical areas and age groups. Data was obtained through focus group, zoom and telephonic interviews to see how past classificatory systems still persist in a democratic South Africa and whether democracy allows people the freedom to choose how they want to be classified. It is a study about cultural identity which aimed to hear the stories from the women themselves, providing space for them to talk about their past as women of colour, their present situations, and how both of these affect them and the cultural identity of future generations. Overarching themes that emerged were that of historical traumas related to colonialism, slavery and apartheid; traumas of having to comply with certain standards of beauty and traumas of place, who we are and our place in the world. This study showed that discussions regarding something as seemingly insignificant as hair is important. Hair is not just hair. It is a journey, a trauma, a story and a huge part of our identity to heal from silenced and untold histories. It is a conversation that must be had. It is a story that must be told.